Simultaneous low friction and ultra-low wear enabled by a 2, 5-Furandicarboxylic acid derived bio-based ionic liquid. (October 2022) - Ruan, Xinxin; Chen, Huanyi; Jiao, Chengcheng; Wei, Xianzhe; Wang, Yandong; Gong, Ping; Song, Lexin; Nishimura, Kazuhito; Yu, Jinhong; Jiang, Nan; Cai, Tao
Abstract: Bio-based protic ionic liquids (bio-PILs) based on 2, 5-Furandicarboxylic acid and polyetheramine was synthesized, which was explored as a neat lubricant and lubricant additive for different alcohols that has different hydroxyl numbers under varied test conditions. Long-term service performance testing showed that the bio-PILs could achieve ultra-low coefficient of friction and wear simultaneously, which decreased coefficient of friction of 95.94% and wear rate of 99.87% compared to dry friction under Si3 N4 -to-steel tribo-pairs. The distinguished tribological performance is contributed to the bio-PILs can absorb on the rubbing surface and form a lubricating protective film to avoid direct contact of super hard upper Si3 N4 ball against lower steel plate. This work presents a facile approach to synthesize high-performance bio-based protic ionic liquids using biomass as bridging agent and provides new insight into the underlying lubricating mechanism, which might help guide the development of novel bio-based lubricants in the future. Highlights: The 2, 5-Furandicarboxylic derived bio-based protic ionic liquids (bio-PILs) was synthesized and identified. The bio-PILs shows excellent thermal stability and anti-corrosion property. Excellent friction reduction (95.94%) and anti-wear performance (99.87%) was obtained simultaneously by bio-PILs. Ultra-low wear rate (5.4305 × 10 −18 m 3 /N m) was achieved under ceramic-to-steel contact.